Development Of Android Application For Tourism Information In Banda Aceh - Mukti Qamal (Faculty of Engineering, Malikussaleh University, 2018)
Banda Aceh is a city where the tourism sector is growing rapidly. The tourists from outside Aceh, especially those who are visiting Banda Aceh for the first time, will have little difficulty in accessing tourist locations in this city because they do not have detail information about the locations. The purpose of this study is to develop a mobile-based Geographic Information System on tourism in Banda Aceh, which can help tourists in choosing the tourist location they want to visit and recommend the nearest route from the user's position to the tourist spot, by using the shortest popular route search algorithm, Dijkstra's algorithm. In addition, this application uses Haversine Formula in calculating the distance between two location on a surface of earth. The results of this study are dual-language android-based applications that can inform tourist locations and display the nearest route from the user's position to the tourist spot.